Knowledge, attitude and practices of medical students on COVID-19 vaccines - Puranik, Akhila; Puranik, Ameya; Priya, Noopur (International Journal Of Community Medicine And Public Health, 2021)
Background: Coronaviruses are a group of related RNA viruses that cause diseases in humans and animals. They cause respiratory tract infections which can be mild to severe and can be life threatening. Mild infection includes some symptoms of common cold while severe cases can cause SARS. Coronaviruses can pneumonia and bronchitis. In December 2019, a pneumonia outbreak was reported in Wuhan, China. The outbreak was traced to a novel strain of coronavirus, which was given the interim name 2019-nCOV by the WHO. Methods: A cross sectional study has been conducted for the period of 7 days on students studying MBBS/BDS/BPT. All the students who participated in the study were vaccinated with Covishield vaccine. A multiple choice KAP related questionnaire was developed and students were instructed to fill the appropriate responses with the help of Google forms. Results: 77 students said that Covishield is a live attenuated vaccine.135 students said that AEFI can be reported on all the above places. 120 students said that Covishield is the most beneficial vaccine in market. 110 students said that intramuscular route of administration is preferred.69% students have experienced ADR post vaccination.180 students said they will advise the patient to get vaccinated. 131 students said active immunization is the best preventive strategy. 66% students said vaccination should be made compulsory. 57% students said Government’s implementation of vaccination program is very satisfactory. Conclusions: Majority of the students have positive outlook towards vaccination. Knowledge of health science students about COVID vaccines need to be given special focus.